Cardiac Awake Extracorporeal Life Support—Bridge to Decision?. Issue 5 (16th January 2015) - Sommer, Wiebke; Marsch, Georg; Kaufeld, Tim; Röntgen, Philipp; Beutel, Gernot; Tongers, Joern; Warnecke, Gregor; Tudorache, Igor; Schieffer, Bernhard; Haverich, Axel; Kühn, Christian
Abstract Severe acute heart failure requires immediate intensive care unit (ICU) treatment, but prognosis and outcome of further treatment regimens largely depends on the preprocedural status of the patient. Especially, multiorgan failure including mechanical ventilation are unfavorable predictors of clinical outcome. Here, we report a strategy of immediate initiation of extracorporeal life support (ECLS) in awake and spontaneously breathing patients with acute heart failure to achieve early multiorgan recovery and gain sufficient time for further treatment planning. Twenty‐three patients with severe cardiac failure refractory to standard medical management underwent ECLS treatment, after first clinical signs of cardiac failure appeared to avoid mechanical ventilation. Hemodynamic parameters and renal and liver functions were monitored. Outcome at 1 and 6 months was determined. Patients 46.1 ± 15.5 years of age were placed on ECLS due to various underlying diagnosis: ischemic heart disease (n = 6), dilatative cardiomyopathy (n = 4), myocarditis (n = 2), graft failure following heart transplantation (n = 6), or other diseases (n = 5). ECLS lasted 11.9 ± 12.9 days. Hemodynamic stabilization was achieved immediately after ECLS initiation. Vasopressors were reduced subsequently and the cardiac situation improved indicated by central venous saturation, which increased from 38.5 ± 11.3% before to 74.26 ± 8.4% (P < 0.0001) 24 h after ECLS initiation. Similarly, serum lactate levels decreased from 4.7 ± 4.6 to 1.7 ± 1.51 mmol/L (P = 0.003). Cumulative 30‐day survival was 87.5%, and 6‐month survival was 70.8%. In acute cardiac failure, early ECLS treatment is a safe, feasible treatment in awake patients allowing a gain of time for final decision. Moreover, this strategy avoids complications associated with sedation and mechanical ventilation and leads to recovery of secondary organ function, enabling destination therapy.